2020
DOI: 10.1186/s12889-020-09752-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between social support status and mortality in a community-based population: a prospective observational study (Yamagata study)

Abstract: Background Social support, defined as the exchange of support in social relationships, plays a vital role in maintaining healthy behavior and mitigating the effects of stressors. This study investigated whether functional aspect of social support is related to 5-year mortality in health checkup participants. Methods This study recruited 16,651 subjects (6797 males, 9854 females). Social support was evaluated using five-component questions: Do you have someone 1) whom you can consult when you are in trouble? … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The study targeted local inhabitants covered by national health insurance, most of whom were agricultural workers, forestry workers, fisheries workers, self-employed, part-time workers, retirees, or unemployed. The details of this study have been reported in a previous study 41 . The eligibility criteria selected participants of local health checkups from 2009 to 2015 who were 40–74 years old.…”
Section: Methodsmentioning
confidence: 99%
“…The study targeted local inhabitants covered by national health insurance, most of whom were agricultural workers, forestry workers, fisheries workers, self-employed, part-time workers, retirees, or unemployed. The details of this study have been reported in a previous study 41 . The eligibility criteria selected participants of local health checkups from 2009 to 2015 who were 40–74 years old.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the classical factors that determine health, social support has been described to have relevant influence on health and mortality [16][17][18]. Moreover, receiving affection can represent a determining factor for good self-perceived health [19], while the lack of social support can be very relevant in some population groups, like the elderly [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…After a 12-month follow-up of people suffering from pain after traffic injuries, dissatisfaction with social life was recognized as a predictor of a non-resilient mental health trajectory [30]. Similar studies reported that social support buffered the negative effects of life adversities [65,70] and stressors on health and revealed a reduction in mortality of up to 50% in those with satisfying social relationships [72,73]. Social isolation has been linked to (epi-)genetic changes in humans, exposing affected individuals to long-term stress-related alterations in mental health and, thus, resilience [74,75].…”
Section: Discussionmentioning
confidence: 83%